Utilizing environmental information and pricing strategies to reduce externalities of tourism: the case of invasive species in the Galapagos. Issue 6 (3rd June 2017) - Mejía, César Viteri; Brandt, Sylvia
ABSTRACT: The increase in demand for nature-based tourism brings economic and educational benefits but risks the introduction of invasive species. Increasing the length of tourist trips can better balance these benefits and risks by maintaining revenues while reducing the number of unique contacts with tourists. Changing the relative prices of trips can induce tourists to take longer trips. We hypothesized that providing information about the negative externalities of tourism could improve the effectiveness of such pricing strategies. We administered one of two discrete choice surveys to tourists considering a trip to the Galapagos. One of the surveys described the Galapagos as a fragile ecosystem susceptible to invasive species; the second described it as a standard nature-based destination. For each sample, we estimated the probability of the tourist choosing a short versus long trip, given the tourist's personal information and trip options presented to him. We then simulated the demand for trips using three pricing strategies. We found that providing information on invasive species significantly increased the efficacy of strategic pricing. We propose using a two-prong approach to tourism management: educate potential tourists about the islands' vulnerabilities, and simultaneously increase the per-day cost of short trips relative to that of longer trips.